Enfoque alternativo para la evaluación de Destrezas con Criterios de Desempeño en Ciencias Sociales, año lectivo 2023-2024 - Díaz Mora, Leonela Rosario (2024)
The assessment, being a fundamental part of the teaching and learning process, is not static, in recent decades it has undergone significant changes, which implies the use of new methodologies, strategies and techniques that allow the diagnosis and analysis of students' abilities or difficulties. to guarantee quality education. Given this particularity, the mandatory education Curriculum of Ecuador 2016, to meet the needs of the current educational reality, establishes the evaluation of Skills with Performance Criteria and motivates the teacher to implement an alternative approach for their evaluation. The proposed objective for this research corresponds to: Determine if in the area of social sciences of Higher Basic General Education of the Cordillera School of Loja city. The evaluation with an alternative approach is considered. The method used is inductive, with a qualitative approach; furthermore, it can be considered exploratory and diagnostic. The instruments used were an interview aimed at teachers and a survey for students. The results of the research allowed us to determine that teachers do not apply an alternative approach to evaluate skills with performance criteria in the subject of Social Sciences. The assessment with an alternative approach evaluates critical thinking, problem solving, creativity, recognizes and stimulates the student's abilities, allows them to be more responsible and build their own learning for everyday life, instead of a simple performance based on memorization. Not using evaluation with an alternative approach limits the potential and abilities of students, by assessing only the cognitive and not considering the attitudinal, affective and procedural level of the student. Keywords: Curriculum Elements, Cognitive Reasoning, Evaluation Methodology, Evaluation Instruments.